Smart Mini Spirometer Monitoring System Based on ESP32 and MQTT Communication Protocol - Elvan Yuniarti; Muhammad Tiorahman Hakim; Thallut Malik Khatam; Irvanza Huga Fausta; Hernanda Thoriq Hermansyah; Edi Sanjaya; Ambran Hartono (Department of Physics, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
A system created can also provide solutions for remote monitoring that can be read through the dashboard on the WEB. Lung health monitoring is very important. This can be used to detect lung disease in its early stages. The parameters used to detect lung health are lung function parameters, especially Forced Vital Capacity (FVC) and Forced Expiratory Volume in one second (FEV1). This study aims to design a smart mini spirometer that can calculate the parameters of PVC and FEV1. The tools and materials used are the pressure sensor, MPX5010DP, venturi pipe, ESP32, 0.96-inch OLED, laptop, Arduino IDE, Message Queuing Telemetry Transport (MQTT) protocol, Web dashboard, and WiFi Internet. The results obtained successfully created a Smart Mini Spirometer Monitoring System. This system has an accuracy performance of 97.5% with a standard volume reference of 3.7 L. The system created can also provide solutions for remote monitoring that can be read via the dashboard on the WEB.